2020
DOI: 10.21203/rs.3.rs-110165/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of Arabidopsis photoreceptor CRY2 by two distinct E3 ubiquitin ligases

Abstract: Cryptochromes (CRYs) are photoreceptors or components of the molecular clock in various evolutionary lineages, and they are commonly regulated by polyubiquitination and proteolysis. Multiple E3 ubiquitin ligases regulate CRYs in animal models, and previous genetics study also suggest existence of multiple E3 ubiquitin ligases for plant CRYs. However, only one E3 ligase, Cul4COP1-SPAs, has been reported for plant CRYs so far. Here we show that Cul3LRBs is the second E3 ligase of CRY2 in Arabidopsis. We demonstr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We reasoned that one such candidate is the COP1 E3 ubiquitin ligase which is part of the CRL4 COP1-SPA complex. Previous studies have shown that COP1 is partially required for the turnover of CRY2 (Figure S5B) (Wang et al 2001;Lau et al 2019;Ponnu et al 2019;Weidler et al 2012;Wang et al 2015;Chen et al 2021).…”
Section: Ubp13 Interacts With Cop1 E3 Ubiquitin Ligase and Increases Its Stability To Mediate The Degradation Of Cry2mentioning
confidence: 83%
See 2 more Smart Citations
“…We reasoned that one such candidate is the COP1 E3 ubiquitin ligase which is part of the CRL4 COP1-SPA complex. Previous studies have shown that COP1 is partially required for the turnover of CRY2 (Figure S5B) (Wang et al 2001;Lau et al 2019;Ponnu et al 2019;Weidler et al 2012;Wang et al 2015;Chen et al 2021).…”
Section: Ubp13 Interacts With Cop1 E3 Ubiquitin Ligase and Increases Its Stability To Mediate The Degradation Of Cry2mentioning
confidence: 83%
“…During seedling emergence from the soil, in a developmental process called photomorphogenesis, CRYs control seedling stem growth relative to the amount of blue light perceived by them. This control of hypocotyl growth depends on the amount of blue light; a higher amount of light results in degradation of CRY2, leading to attenuation of its signaling, and a lower light amount results in accumulation of CRY2 (Pedmale et al 2016;Yu et al 2007;Chen et al 2021). CRY2 levels thus finetune growth in response to light levels; and so, it is essential to understand mechanisms that control CRY2 turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation